Tissue Factor Localization in Non-Human Primate Cerebral Tissue - del Zoppo, Gregory J; Yu, Jian-Qing; Copeland, Brian R; Thomas, Winston S; Schneiderman, Jacob; Morrissey, James H (Thrombosis and Haemostasis, 1992)
Tissue factor (TF), the principal procoagulant of human brain, resides in specific regions of the non-human primate central nervous system. Immunohistochemical studies employing murine anti-human TF monoclonal antibodies (MoAbs) detected TF antigen in the cortex, basal ganglia, cerebellum, and cervical spinal cord in three normal baboon subjects. Although significantly less prominent than human cortical gray matter, a distinct partition of TF in gray matter >white matter was noted. The gray matter predilection of TF was confirmed in primate temporal and parietal lobe cortex by both sandwich ELISA and one-stage coagulation assay. Variation in the relative quantity of TF antigen was observed by ELISA among the three subjects studied. Procoagulant activity followed the pattern of TF antigen (cortical gray matter >basal ganglia ≥cerebellum >cortical white matter), and was 96.5–98.5% inhibitable by a function inhibiting anti-human TF MoAb combination. TF antigen was associated with the microvasculature of all cerebral tissues studied, and spared capillaries most selectively in the cerebral cortex, basal ganglia, and cerebellum. These findings suggest a highly specific ordering of TF antigen and related procoagulant activity in the central nervous system of the baboon, confined primarily to gray matter parenchyma, and to the non-capillary microvasculature.